High local unemployment and increased mortality in Danish adults; results from a prospective multilevel study. Issue 11 (22nd October 2003) - Osler, M; Christensen, U; Lund, R; Gamborg, M; Godtfredsen, N; Prescott, E
Abstract : Aims: To examine the relation between unemployment rates in area of residence and all-cause mortality, taking the individuals' unemployment experience and a number of social and behavioural factors into account. Methods: Prospective cohort study with record linkage to mortality and unemployment registers. Data were pooled data from two population studies conducted in Copenhagen, Denmark. The association between unemployment at parish level and mortality was examined in Cox proportional hazard analysis. A total of 15 980 men and women, aged 20–67 years and employed at 1 January 1980, were studied. All-cause mortality was followed from January 1981 to December 1998. Results: The unemployment rate in the area of residence was associated with increased mortality (hazard ratiohighest v lowest quartile 1.35:0.14–1.60) even after adjustment for individuals' unemployment experience in 1980, which was also a risk factor (hazard ratioyes/no 1.38:1.16–1.64). These estimates attenuated somewhat when other social and behavioural covariates were taken into account. The effects were similar in men and women, but the influence of individuals' unemployment experience during one and five years decreased gradually with increasing age. Conclusion: This prospective study suggests that high local unemployment and individuals' experience of unemployment increase mortality risk, even after adjustment for other social and behavioural factors.